Hedonic, Instrumental, and Normative Motives: Differentiating Patterns for Popular, Accepted, and Rejected Adolescents - Dijkstra, Jan Kornelis; Kretschmer, Tina; Lindenberg, Siegwart; Veenstra, René (Journal of Early Adolescence, 2015)
This study examined to what extent motives for behavior differentiated between popular, accepted, and rejected adolescents. Based on goal-framing theory, three types of motives were distinguished: hedonic (aimed at short-term gratification), instrumental (aimed at improvement of one’s situation), and normative (aimed at acting in accordance with what one thinks one is ought to do) motives, which were based on teachers’ assessments. These motives were related to peer-reported popularity, acceptance, and rejection in a sample of adolescent boys (n = 287) and girls (n = 303; X¯age = 13.51; SD = 0.54). Results showed that popular adolescents were mainly characterized by instrumental and normative motives. Accepted adolescents were high in hedonic and normative motives, but low in instrumental motivation, whereas rejected adolescents showed the exact opposite pattern. These results indicate that being successful among peers is not only a matter of behavior but also of motives underlying behaviors.
CRIS-Team Scopus Importer:2025-03-19
Keywords: acceptance; goals; motives; popularity; rejection; sociometric status